Peranan Hakim untuk Mendamaikan Para Pihak yang Bersengketa dalam Perkara Perdata di Pengadilan Negeri Denpasar - Made Rai Diascitta Hardi Sentana; I Wayan Wesna Astara; I Nyoman Gede Sugiartha (Jurnal Analogi Hukum, 2020)
The peace agreement between the two parties on a voluntary basis for mutual yield or relinquish a portion of its rights to prevent things. This research aims to know two things, namely, first, to know the role of judges in reconciling the parties in a civil lawsuit and the second, to know the power of the law ruling in the case of civil peace. This research was carried out at the Denpasar District Court by using method of empirical research and purposive technique. Analysis of the data of this research was done qualitatively. Based on the results of the interviews with District Court Judges Denpasar, Denpasar District Court, the Registrar and the lawyers (Advocates) then this research it can be concluded that the first, judges have the role and obligation to reconcile the parties in dispute before it is exposed to the Court of session and the form of the verdict of peace is a peace act having the force of law as the verdict.